PERUBAHAN BEBERAPA SIFAT KIMIA TANAH AKIBAT PEMBERIAN LIMBAH CAIR INDUSTRI KELAPA SAWIT DENGAN METODE LAND APPLICATION - Zulkarnain . (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
The aims of the research was to know effect gift industrial liquid waste of palm oil with the method land application on the some soil chemistry properties.The research was started from April until July 2011, that conducted in PT. London Sumatra sub district of Tanjung Isuy, with total areas of land was + 7,29 ha at block 81 D and waste volume given as much 6.690 m3 equivalent by 6.6690.000 litre.  Soil sample was taken by using auger soil at depth of 0-20 cm and 20-40 cm compositely by system random.Results of the research showed that gift industrial liquid waste of palm oil with the method land application was existence of degradation of pH, C organic, and N total, but improvement on the element P available and K available.